Sialic acid biosensing by post-printing modification of PEDOT:PSS with pyridylboronic acid - Hideki Fujisaki; Akira Matsumoto; Yuji Miyahara; Tatsuro Goda (Science and Technology of Advanced Materials)
A poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)-based conducting polymer, which has biorecognition capabilities, has promising biosensing applications. Previously, we developed a facile method for post-printing chemical modification of PEDOT:PSS thin films from commercial sources. Molecular recognition elements were directly introduced into the PSS side chain by a two-step chemical reaction: introduction of an ethylenediamine linker via an acid chloride reaction of the sulfonate moiety, and subsequent receptor attachment to the linker via amine coupling. In this study, the same method was used to introduce 6-carboxypyridine-3-boronic acid (carboxy-PyBA) into the linker for specifically detecting N-acetylneuraminic acid (sialic acid, SA), as a cancer biomarker. The surface-modified PEDOT:PSS films were characterized by X-ray photoelectron spectroscopy, attenuated total reflection Fourier-transform infrared spectroscopy, and static water contact angle and conductivity measurements. The specific interaction between PyBA and SA was detected by label-free reagent-free potentiometry. The SA-specific negative potential responses of modified PEDOT:PSS electrodes, which was ascribed to an SA carboxyl anion, were observed in a physiologically relevant SA range (1.6–2.9 mM) at pH 5, in a concentration-dependent manner even in the presence of 10% fetal bovine serum. The sensitivity was −2.9 mV/mM in 1–5 mM SA with a limit of detection of 0.7 mM. The sensing performances were almost equivalent to those of existing graphene-based electrical SA sensors. These results show that our chemical derivatization method for printing PEDOT:PSS thin films will have applications in SA clinical diagnostics.